Self-repairing concrete based on fiber modification and preparation method thereof

Through the combination of modified basalt fibers and Bacillus paste, the problem of degradation of mechanical properties in traditional self-repaired concrete is solved, more efficient crack repair and microbial survival is achieved, and the self-repairing ability and mechanical properties of hydraulic concrete are improved.

CN120518360APending Publication Date: 2025-08-22CHINA THREE GORGES UNIV
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202510692688.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-05-27
Publication Date
2025-08-22

AI Technical Summary

Technical Problem

After the traditional self-repairing concrete is incorporated into microorganisms, the mechanical properties of the concrete are reduced, and the survival rate and repair efficiency of the microorganisms are not high, making it difficult to effectively repair cracks in hydraulic concrete.

Method used

Modified basalt fibers and Bacillus paste are used to modify the basalt fibers, and the expanded perlite is used as a carrier to solidify microorganisms, combined with fly ash and other materials to form a three-dimensional network structure, which improves the adhesion and survival ability of microorganisms and enhances the self-healing effect.

Benefits of technology

The three-dimensional mesh structure formed by modified basalt fibers reduces the shrinkage stress caused by moisture evaporation, prevents cracks from spreading, and microorganisms maintain activity in high alkali environments, improves the crack repair ability and mechanical properties of self-healing concrete, and reduces production costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120518360A_ABST
    Figure CN120518360A_ABST
Patent Text Reader

Abstract

The invention provides self-repairing concrete based on fiber modification. The self-repairing concrete is prepared from the following components in parts by weight: 750 to 800 parts of bacterium-carrying particles, 500 to 800 parts of modified basalt fiber, 870 to 1140 parts of water, 2700 to 2850 parts of cement, 650 to 720 parts of fly ash, 7100 to 7600 parts of sand, 113400 to 115400 parts of stone, 55 to 80 parts of calcium lactate, 19 to 25 parts of water reducing agent, 9 to 14 parts of urea and 1 to 5 parts of air entraining agent. The basalt fiber is modified by adopting the nanoparticles, so that more attachment sites and nucleation paths are provided for the growth of bacillus pasteurii, the self-repairing capability of the concrete is improved, and the durability of the concrete is remarkably improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of concrete materials, and in particular to a self-repairing concrete based on fiber modification and a preparation method thereof. Background Art

[0002] Concrete is widely used in hydraulic engineering due to its advantages such as high compressive strength, low cost and good durability. However, hydraulic concrete is very prone to cracks due to the influence of external environmental factors, which poses a hidden danger to the durability of concrete and the safety of hydraulic structures. At present, crack self-repairing technology has received widespread attention both at home and abroad. Traditional self-repairing concrete is achieved by pre-adding microorganisms into the concrete. When cracks appear in the concrete structure and foreign substances enter the concrete, the microorganisms will be "awakened" and the crack self-repair mechanism will be activated. However, in order to ensure the survival rate of microorganisms in concrete, the microorganisms are usually immobilized and coated. However, incorporating microorganisms into concrete in an immobilized manner will have a negative impact on the mechanical properties of concrete, such as strength. Therefore, the present invention incorporates modified basalt (BF) fiber and polyacrylonitrile (PAN) fiber respectively when preparing self-repairing concrete. Although scholars have applied basalt fiber and bacteria to microbial self-repairing concrete and found that basalt fiber can effectively promote crack repair, the surface of basalt fiber lacks hydrophilic groups, which makes basalt fiber hydrophobic and electronegative, while the surface of most bacteria in the solution is negatively charged, which is not conducive to the attachment and deposition of bacteria on basalt fiber. The present invention modifies the basalt fiber to compensate for the above problems and also compensates for the mechanical properties reduced by the solid coating treatment of microorganisms when preparing self-repairing concrete. Moreover, since the porous surface of the fiber can serve as an attachment carrier for microorganisms, the survival time of microorganisms is further extended and the mineralization and deposition efficiency of microorganisms is improved.

[0003] For example, CN112500074A discloses a microbial self-repairing concrete and its preparation method. This application relates to the field of concrete and specifically discloses a microbial self-repairing concrete comprising the following components by weight: 860-980 parts coarse aggregate, 630-760 parts fine aggregate, 320-360 parts cement, 40-55 parts microsilica fume, 140-180 parts mineral powder, 140-160 parts water, 7-9 parts sodium aminosulfonate water reducer, 11-13 parts urea, 13-15 parts calcium chloride, and 85-100 parts of a carrier coated with an anaerobic crack-healing agent, the crack-healing agent being an anaerobic Bacillus pasteurianus solution. The microbial self-repairing concrete disclosed in this application has the ability to self-repair concrete cracks in an anoxic environment. In this invention, the microbial survival is effectively guaranteed through the immobilization and coating treatment. However, adding microorganisms to concrete only in the form of solid loads will have an adverse effect on the mechanical properties of concrete such as compressive strength and splitting strength, resulting in a decrease in concrete strength.

[0004] In response to the above problems, the present application provides a self-repairing concrete based on fiber modification and a preparation method thereof. By incorporating fibers into the self-repairing concrete, the impact of microbial loading on the mechanical properties of concrete is compensated, while the crack repair ability of the self-repairing concrete is improved. Summary of the Invention

[0005] To solve the above technical problems, the present invention provides a fiber-modified self-repairing concrete, comprising the following components: 750-800 parts of bacteria-carrying particles, 500-800 parts of modified basalt fiber, 870-1140 parts of water, 2700-2850 parts of cement, 650-720 parts of fly ash, 7100-7600 parts of sand, 113400-115400 parts of gravel, 55-80 parts of calcium lactate, 19-25 parts of water reducer, 9-14 parts of urea, and 1-5 parts of air-entraining agent.

[0006] The preparation method of the modified basalt fiber is: S1 pretreatment: using H2O2 solution to oxidize the surface of basalt fiber, stirring and oxidizing, washing and drying to a certain weight; the dried fiber is etched in an acid solution, washed and dried after the reaction to obtain a pretreated fiber; S2. Modification: Add nanoparticles to an ethanol solution of a silane coupling agent, stir to form a suspension, react the fibers pretreated in S1 with the suspension, and dry to obtain modified basalt fibers.

[0007] The acid solution in S1 includes hydrochloric acid and an organic acid, wherein the organic acid is at least one of malic acid and tartaric acid, and the concentration of each acid is 0.1-0.8 mol / L.

[0008] S2 The nanoparticles are at least one of nano-SiO2 or nano-CaO, preferably nano-SiO2 and nano-CaO; the mass ratio of the nanoparticles to the basalt fiber is 1: (5-10).

[0009] Both S1 and S2 are carried out at 20-30° C.; in S2, the pretreated fibers react with the suspension under ultrasonic conditions at an ultrasonic frequency of 25-35 kHz.

[0010] The bacteria-carrying particles are expanded perlite containing Bacillus pasteurianus liquid, and the preparation method is as follows: S1. Using a vacuum impregnation method, the Bacillus pasteurianus solution was adsorbed on the surface and pores of expanded perlite with a particle size of 2.36~4.75mm and dried; S2. A coating slurry was prepared in a ratio of 2.31:1.00:1.05 of metakaolin: water: sodium silicate aqueous solution, with a sodium silicate aqueous solution concentration of 0.1 to 0.5 mol / L. The expanded perlite treated with S1 was sprayed with the coating slurry, repeatedly flipping and spraying 3 to 4 times, and dried to obtain bacterial-loaded granules. The absorbance OD of the Bacillus pasteurianus liquid 600 It is 0.2~0.8.

[0011] The preparation method of the Bacillus pasteurianus bacterial liquid is as follows: (1) Prepare solid culture medium: casein peptone 15 g / L, soy peptone 5 g / L, urea 20 g / L, agar powder 20 g / L; Prepare liquid culture medium: casein peptone 15 g / L, soy peptone 5 g / L, urea 20 g / L; After preparation, the culture medium was sterilized by high-pressure steam, and its pH value was adjusted after cooling. The pH value of the liquid culture medium was adjusted to 11, and the pH value of the solid culture medium was adjusted to 8, 9, 10, 11, 12, and 13 respectively; (2) dropping a suspension of Bacillus pasteurianus onto the solid culture medium with a pH of 8 prepared in step (1), and culturing the culture medium at a constant temperature of 30°C for 48 hours to obtain a Bacillus pasteurianus sample; (3) The Bacillus pasteurianus sample obtained in step (2) is continuously inoculated onto a solid culture medium with a pH value of 9. According to this step, the Bacillus pasteurianus is continuously inoculated onto a solid culture medium with a higher alkalinity. After each inoculation, the culture is cultured at the same constant temperature of 30°C for 48 hours. This cycle is repeated until the Bacillus pasteurianus can grow well on the high alkalinity flat culture medium with a pH value of 13, and the acclimation of the Bacillus pasteurianus to alkalinity resistance to pH value 13 is successfully completed. (4) The Bacillus pasteurianus sample plate coated on the solid culture medium with a pH of 13 was inoculated into the liquid culture medium with a pH of 11. The inoculated culture medium was placed in a constant temperature shaking incubator and cultured at 120 r / min at 30°C for 48 hours to obtain the Bacillus pasteurianus bacterial liquid.

[0012] The cement is PO42.5 ordinary Portland cement, and the fly ash is Class II fly ash.

[0013] Among the stones, the mass ratio of small stones to medium stones is 4:6; the fineness modulus of the small stones is 2.69-2.73, and the average particle size is 0.35~0.5cm; the particle size of the medium stones is 5~20mm.

[0014] The preparation method of the self-repairing concrete comprises the following steps: mixing 750-800 parts of bacteria-carrying particles, 500-800 parts of modified basalt fibers, 870-1140 parts of water, 2700-2850 parts of cement, 650-720 parts of fly ash, 7100-7600 parts of sand, 113400-115400 parts of gravel, 55-80 parts of calcium lactate, 19-25 parts of a water reducer, 9-14 parts of urea, and 1-5 parts of an air-entraining agent; stirring the mixture evenly; and pouring the mixture into a mold. After the test piece is formed, the mixture is cured to obtain the self-repairing concrete.

[0015] The beneficial effects of the present invention are as follows: 1. The basalt (BF) fiber used in this invention forms a three-dimensional network structure during the initial setting of concrete, reducing shrinkage stress caused by water evaporation and making cracks finer and more dispersed, facilitating effective microbial filling. The bridging effect of the basalt fiber prevents rapid crack expansion, allowing the self-repair mechanism more time to precipitate calcium carbonate, thereby improving the repair rate. The chemical composition of basalt fiber (SiO2, Al2O3) is weakly alkaline in the cement matrix, which is conducive to the survival of Bacillus pasteurianus. Modification of the basalt fiber provides more nucleation sites and growth pathways for the self-healing microorganisms, ensuring that the fiber maintains its structural morphology and excellent mechanical properties in concrete over the long term.

[0016] 2. The Bacillus pasteurianus used in this invention is a facultative anaerobic microorganism that is well-suited to the hypoxic or anaerobic working environment of hydraulic concrete, allowing the incorporated microorganisms to better exert their effects. Bacillus pasteurianus also possesses a certain ability to resist mechanical extrusion and friction. During the concrete preparation process, these properties can synergize with each other to effectively ensure the survival of microorganisms.

[0017] 3. This study used plates with varying alkalinity levels to conduct alkali tolerance experiments on Bacillus pasteurianus. After acclimation, the microorganism's alkali tolerance was significantly enhanced. When applied to concrete, the acclimated microorganisms effectively reduced damage to the microorganisms caused by the high alkalinity environment within the concrete, improving their viability and activity.

[0018] 4. The supporting material used in this invention is expanded perlite, which exhibits excellent compatibility with cement-based materials. Expanded perlite possesses a certain strength and does not excessively weaken the concrete during concrete preparation, significantly reducing any negative impact on concrete strength. Using expanded perlite to support Bacillus pasteurianus provides ample living space for the microorganism. The high alkaline environment within concrete typically negatively impacts microbial activity, but this supporting method effectively mitigates this negative impact, allowing the microorganisms to maintain good activity in a relatively stable environment. The carrier selected in this invention has a particle size range of 2.36 to 4.75 mm. Within this specific particle size range, the carrier has a large tearing area. This large tearing area plays a key role in the release of microorganisms, ensuring their effective release and thus fully realizing their effectiveness in related applications. The carrier particles are coated with a mixed slurry of metakaolin, sodium silicate solution, and water, preventing the loss of microorganisms within the carrier and reducing the impact of the external environment on the microorganisms.

[0019] 5. The addition of fly ash in this invention effectively improves the quality of hydraulic concrete. While maintaining concrete performance, it significantly reduces the amount of cement and fine aggregate used, thereby lowering production costs. Furthermore, it improves the workability of concrete, reduces heat generated during hydration, and reduces stress within the concrete caused by temperature fluctuations, thereby extending the service life of hydraulic concrete structures.

[0020] 6. The sand selected in this invention possesses excellent gradation properties. This high-quality graded sand exhibits significant advantages in the concrete production process: on the one hand, it can effectively reduce the amount of cement used, lowering material costs while maintaining concrete strength and other properties; on the other hand, it can also reduce the amount of water used in the mixture, facilitating the production of concrete with better fluidity, density, and uniformity. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 Preparation flow chart of the present invention.

[0022] Figure 2 The liquid culture medium described in Example 1.

[0023] Figure 3 The solid culture medium described in Example 1. DETAILED DESCRIPTION

[0024] The embodiments of the present invention will be described in detail below with reference to examples. The following examples are only used to illustrate the present invention and should not be construed as limiting the scope of the present invention.

[0025] Example 1 Preparation of bacteria-loaded particles: (1) Prepare liquid culture medium (attached) according to 15g / L casein peptone, 5g / L soy peptone, 20g / L urea, and 20g / L agar powder. Figure 2 ) and solid culture medium (with Figure 3 ), agar powder needs to be added when preparing solid culture medium, but agar powder is not required for liquid culture medium. After preparation, the culture medium is transferred to a high-pressure steam cooker for high-pressure steam sterilization. The sterilization temperature is 121°C, the sterilization time is 20 minutes, and the sterilization equipment is an XFS-280CB+ vertical high-pressure steam sterilizer. After sterilization, the culture medium is removed from the high-pressure steam cooker, allowed to cool, and then its pH value is adjusted. The pH value of the liquid culture medium is adjusted to 11, and the pH value of the solid culture medium is adjusted to 8, 9, 10, 11, 12, and 13 respectively for the subsequent microbial pouring plate in step 3.

[0026] (2) Bacillus pasteurianus was stored in a 5 ml ampoule in the form of freeze-dried powder and vacuum dried. The outer surface of the glass inner tube in the ampoule was wiped with cotton soaked in 70% alcohol, and then the tip of the outer tube was heated over the flame of an alcohol lamp. Sterile water was pipetted onto the tip of the heated outer tube with a pipette to break the outer tube. Finally, 0.5 ml of sterile water was pipetted into the tube and slightly shaken until the freeze-dried powder was evenly suspended. 0.2 ml of the bacterial suspension was dropped onto the solid culture medium with a pH of 8 prepared in step 1. The plate after coating was sealed with a sealing film and placed in a constant temperature environment at 30 °C for 48 h to obtain a Bacillus pasteurianus sample.

[0027] (3) The Bacillus pasteurianus sample obtained in step 2 was inoculated onto a solid culture medium with a pH value of 9 in the same manner as in step 2. Following this procedure, Bacillus pasteurianus was continuously inoculated onto a flat solid culture medium with a higher alkalinity. After each inoculation, the culture was cultured at the same constant temperature of 30°C for 48 hours. This cycle was repeated until Bacillus pasteurianus could grow well on a high alkalinity flat culture medium with a pH of 13, successfully completing the acclimation of Bacillus pasteurianus to alkalinity resistance to pH 13.

[0028] (4) In a sterile operating box, inoculate the Bacillus pasteurianus sample plate coated on a solid culture medium with a pH of 13 into a liquid culture medium with a pH of 11. Place the inoculated culture medium in a constant temperature shaking incubator and culture it at 120 r / min at 30°C for 48 hours to obtain a Bacillus pasteurianus bacterial liquid and preserve it.

[0029] (5) Centrifuge the Bacillus pasteurianus liquid in a centrifuge to obtain bacterial sludge, and measure its absorbance OD 600 , OD 600 The value should be 0.2~0.8, such as the bacterial solution OD 600 If the value exceeds this range, the bacterial solution needs to be diluted with pure water until the OD 600 The value is in the range of 0.2~0.8. At this time, the bacterial solution concentration is calculated as follows: Y=8.59×Z 1.3627 ×10 7 In the formula, Y is the bacterial concentration, cells / mL; Z is the OD600 absorbance, and the value is between 0.2 and 0.8.

[0030] The centrifuged bacterial suspension and expanded perlite (particle size 2.36-4.75 mm) were placed in a vacuum barrel. 300 mL of bacterial suspension was added to 1 kg of carrier. An air compressor was used to evacuate the air from the barrel to reduce the pressure to -0.06 MPa. The suspension was adsorbed onto the surface and pores of the expanded perlite (particle size 2.36-4.75 mm) using a vacuum impregnation method at -0.06 MPa. After adsorption, the carrier particles were dried in an oven (40 ± 2°C) to constant weight.

[0031] (6) After drying, the coating material is used for coating. The specific coating steps are as follows: The coating slurry was prepared in the ratio of metakaolin: water: sodium silicate aqueous solution = 2.31:1.00:1.05, wherein the concentration of the sodium silicate aqueous solution was 0.1 mol / L; the coating slurry was poured into a spray barrel and sprayed on the surface of the expanded perlite treated in step (5), repeatedly turning it over and spraying it 3 to 4 times, and then placed at room temperature to dry for a day and a night, and then dried in an environment of 40±2°C to constant weight to obtain bacteria-loaded particles.

[0032] Example 2 Preparation of modified basalt fiber: (1) Pretreatment of basalt fiber: 50 g of basalt fiber was surface-oxidized with 200 ml of 5% H2O2, stirred and oxidized for 2 h, washed with distilled water, and dried at 60 °C to a constant weight. The dried fiber was etched in 100 mL of 1 mol / L HCl solution for 90 min, washed with deionized water until the pH reached 7, and then dried in an oven. Oxidation and etching were performed at 25 °C.

[0033] (2) Modification of basalt fiber: 1.5 g of silane coupling agent KH-550 was dispersed in 200 mL of 95% ethanol and stirred for 30 min to ensure that KH-550 was fully dissolved. 6 g of nano-SiO2 was added to the solution and stirred for 30 min to form a suspension. In an ultrasonic disperser, the ultrasonic frequency was adjusted to 30 kHz. The pretreated fiber was fully reacted with the above medium at room temperature. After suspension for 30 min, it was dried to obtain SiO2-modified basalt fiber.

[0034] Example 3 Preparation of modified basalt fiber: (1) Pretreatment of basalt fiber: 50 g of basalt fiber was surface-oxidized with 200 ml of 5% H₂O₂, stirred and oxidized for 2 h, washed with distilled water, and dried at 60°C to a constant weight. The dried fiber was etched in 100 mL of a mixed acid solution for 90 min, washed with deionized water until the pH reached 7, and then dried in an oven. Oxidation and etching were performed at 25°C.

[0035] The mixed acid solution is a mixture of hydrochloric acid and malic acid, with a hydrochloric acid concentration of 0.6 mol / L and a malic acid concentration of 0.1 mol / L.

[0036] (2) Modification of basalt fiber: 1.5 g of silane coupling agent (KH-550) was dispersed in 200 mL of 95% ethanol and stirred for 30 min to ensure that KH-550 was fully dissolved. 6 g of nano-SiO2 was added to the solution and stirred for 30 min to form a suspension. In an ultrasonic disperser, the ultrasonic frequency was adjusted to 30 kHz. The fiber pretreated in step (1) was fully reacted with the above medium at room temperature. The suspension was suspended for 30 min and then dried to obtain modified basalt fiber.

[0037] Example 4 The difference from Example 3 is that the mixed acid solution is a mixture of hydrochloric acid and tartaric acid, the hydrochloric acid concentration is 0.5 mol / L, and the tartaric acid concentration is 0.2 mol / L; the rest is the same as Example 3.

[0038] Example 5 The difference from Example 3 is that the mixed acid solution is a mixture of hydrochloric acid, malic acid and tartaric acid, the concentration of hydrochloric acid is 0.4 mol / L, the concentration of malic acid is 0.1 mol / L, and the concentration of tartaric acid is 0.2 mol / L; the rest is the same as Example 3.

[0039] Example 6 The difference from Example 5 is that 6g of nano-SiO2 is replaced by 3g of nano-SiO2+3g of nano-CaO, and the rest is the same as Example 5.

[0040] Example 7 The difference from Example 5 is that 6g of nano-SiO2 is replaced by 5g of nano-SiO2+1g of nano-CaO, and the rest is the same as Example 5.

[0041] Example 8 750 parts of the bacteria-loaded particles prepared in Example 1, 500 parts of the modified basalt fiber prepared in Example 2, 960 parts of water, 2810 parts of cement, 720 parts of fly ash, 7530 parts of sand, 114600 parts of gravel, 75 parts of calcium lactate, 14 parts of urea, 25 parts of high-efficiency polyhydroxy acid water reducer, and 3 parts of AIR202 air entraining agent were put into a mixer and stirred evenly. The mixture was then poured into a mold coated with a release agent. After the specimen was formed, it was placed in an environment of 20±2°C for immersion in water for curing to obtain the self-healing concrete.

[0042] The cement is PO42.5 ordinary Portland cement, and the fly ash is Class II fly ash.

[0043] Among the stones, the mass ratio of small stones (fineness modulus is 2.71, average particle size is 0.35-0.5cm) to medium stones (particle size is 5-20mm) is 4:6.

[0044] The maximum crack width test method is: use the ZW-C3600 image microscope to observe the crack observation points of the concrete specimens, observe the surface closure effect of the cracks of each group of specimens at the curing age of 0, 7, 14, and 28 days, measure and record the surface width changes of the crack observation points, and the maximum repair width of the concrete crack is measured to be 0.77mm.

[0045] The prepared concrete was immersed in a 5% NaOH solution by mass for 180 days. The solution surface was more than 2 cm higher than the specimen surface. After immersion for 180 days, the concrete was taken out and then its compressive strength was measured using a WAW-1000 electro-hydraulic servo universal material testing machine. The descent speed of the testing machine was controlled by displacement, and loading was performed at a speed of 0.6 mm / min. Loading was stopped when the specimen reached 65% of its maximum bearing capacity. Finally, the compressive strength value of the concrete was obtained, which was 43.2 MPa.

[0046] Example 9 Unlike Example 8, the modified basalt fiber uses the fiber prepared in Example 3. At this time, the maximum repair width of the concrete crack is 0.98 mm. After the concrete prepared in this example is soaked in NaOH for 180 days in the same manner as in Example 8, its compressive strength is 51.3 MPa.

[0047] Example 10 The difference from Example 8 is that the modified basalt fiber uses the fiber prepared in Example 4. At this time, the maximum repair width of the concrete crack is 1.02 mm. After the concrete prepared in this example is soaked in NaOH for 180 days in the same manner as in Example 8, its compressive strength is 50.6 MPa.

[0048] Example 11 Unlike Example 8, the modified basalt fiber uses the fiber prepared in Example 5. At this time, the maximum repair width of the concrete crack is 1.16 mm. After the concrete prepared in this example is soaked in NaOH for 180 days in the same manner as in Example 8, its compressive strength is 56.7 MPa.

[0049] Example 12 Different from Example 8, the modified basalt fiber uses the fiber prepared in Example 6, and the maximum repair width of the concrete crack is 1.18 mm; after the concrete prepared in this example is soaked in NaOH for 180 days in the same manner as in Example 8, its compressive strength is 71.2 MPa.

[0050] Example 13 The difference from Example 8 is that the modified basalt fiber is the fiber prepared in Example 7. After the concrete prepared in this example is soaked in NaOH for 180 days in the same manner as in Example 8, its compressive strength is 67.3 MPa.

[0051] Comparative Example 1 Unlike Example 8, no modified basalt fiber was added, and all other conditions were the same as in Example 8. In this case, the maximum repair width of the concrete crack was 0.45 mm. Because the bridging effect of the fiber was lost, the self-repair relied solely on the microbial urease reaction to produce calcium carbonate precipitation. Therefore, the repair effect was inferior to that of the example in which modified fiber was added.

[0052] The basalt fiber (BF) raw material selected in the above embodiment has a density of 2.65 g / cm³, a length of 12 mm, a tensile strength of 1256 MPa, an elastic modulus of 76.1 GPa, and an elongation at break of 3.01%.

[0053] It can be seen from the data of the comparative examples and embodiments that the addition of modified basalt fiber is beneficial to improving the self-repairing ability of concrete. This is because by incorporating the fiber into the self-repairing concrete, the three-dimensional network structure of the fiber reduces the shrinkage stress caused by water evaporation, making the cracks finer and more dispersed, which is conducive to the self-repair of the cracks; at the same time, the bridging effect of the fiber can prevent the cracks from expanding rapidly, giving the self-repair mechanism more time to precipitate calcium carbonate and improve the repair rate.

[0054] As can be seen from Examples 8-11, the mixed acid etching system is beneficial for improving the self-repairing ability of concrete. In the modification process of basalt fiber, the present invention innovatively introduces a mixed acid etching system, combining hydrochloric acid with malic acid and / or tartaric acid to work synergistically, controlling the etching rate and promoting more uniform etching of the fiber surface. This provides more uniform coupling sites for subsequent coupling modification, further optimizing the nucleation sites and growth paths of bacteria, and thus improving the self-repairing ability of concrete.

[0055] It can also be seen from the above embodiments and comparative examples that, during coupling modification, the introduction of nanoparticles SiO2 can increase the roughness of the fiber surface and provide attachment sites for bacteria; the introduction of nano-CaO can further improve the service life of concrete. This is because when basalt fiber is in an alkaline environment for a long time, -OH will destroy the Si-O structure in the fiber skeleton; after the introduction of CaO, a -Si-Ca- film structure will be formed through a hydration reaction, which will weaken the corrosive effect of -OH and thus improve the durability of the concrete.

[0056] In addition, when preparing concrete, microorganisms are immobilized by expanded perlite, and then the immobilized microbial particles are coated with coating materials, which improves the long-term survival rate and microbial release capacity of microorganisms inside the concrete, ensures their mineralization and deposition efficiency, and thus better realizes the self-repair of hydraulic concrete cracks.

[0057] The present invention utilizes the strong oxidizing property of H2O2 to remove grease, pollutants and weak crystalline layers on the surface of basalt fiber, and at the same time introduces polar groups such as hydroxyl (-OH) and carboxyl (-COOH) to improve the surface activity of the fiber.

[0058] The raw material ratio of the present invention is simple and clear, easy to obtain and measure, the process flow is highly standardized, the operation is simple and easy, the professional requirements for the implementation personnel are relatively low, and the training cost is low. In terms of economy and environmental protection, the material cost control of the present invention is excellent, the input-output ratio is significant, the production process is green and environmentally friendly, there is no emission of harmful substances, the environmental impact throughout the life cycle is small, and it is in line with the concept of sustainable development. In terms of wide application, the present invention is adaptable to a variety of engineering environments and application scenarios, can meet the needs of projects of different scales, and has good scalability and compatibility. Overall, the present invention has the conditions for industrial application and is expected to have a broad and far-reaching impact in multiple fields.

Claims

1. A self-repairing concrete based on fiber modification, characterized in that: It includes the following components: 750-800 parts of bacteria-carrying particles, 500-800 parts of modified basalt fiber, 870-1140 parts of water, 2700-2850 parts of cement, 650-720 parts of fly ash, 7100-7600 parts of sand, 113400-115400 parts of gravel, 55-80 parts of calcium lactate, 19-25 parts of water reducer, 9-14 parts of urea, and 1-5 parts of air entraining agent.

2. The self-repairing concrete according to claim 1, characterized in that The preparation method of the modified basalt fiber is: S1 pretreatment: using H2O2 solution to oxidize the surface of basalt fiber, stirring and oxidizing, washing and drying to a certain weight; the dried fiber is etched in an acid solution, washed and dried after the reaction to obtain a pretreated fiber; S2. Modification: Add nanoparticles to an ethanol solution of a silane coupling agent, stir to form a suspension, react the fibers pretreated in S1 with the suspension, and dry to obtain modified basalt fibers.

3. The self-repairing concrete according to claim 2, characterized in that The acid solution in S1 includes hydrochloric acid and an organic acid, wherein the organic acid is at least one of malic acid and tartaric acid, and the concentration of each acid is 0.1-0.8 mol / L.

4. The self-repairing concrete according to claim 2, characterized in that S2 The nanoparticles are at least one of nano-SiO2 or nano-CaO, preferably nano-SiO2 and nano-CaO; the mass ratio of the nanoparticles to the basalt fiber is 1: (5-10).

5. The self-repairing concrete according to claim 2, characterized in that Both S1 and S2 are carried out at 20-30° C.; in S2, the pretreated fibers react with the suspension under ultrasonic conditions at an ultrasonic frequency of 25-35 kHz.

6. The self-repairing concrete according to claim 1, characterized in that The bacteria-carrying particles are expanded perlite containing Bacillus pasteurianus liquid, and the preparation method is as follows: S1. Using a vacuum impregnation method, the Bacillus pasteurianus solution was adsorbed on the surface and pores of expanded perlite with a particle size of 2.36~4.75mm and dried; S2. A coating slurry was prepared in a ratio of 2.31:1.00:1.05 of metakaolin: water: sodium silicate aqueous solution, with a sodium silicate aqueous solution concentration of 0.1 to 0.5 mol / L. The expanded perlite treated with S1 was sprayed with the coating slurry, repeatedly flipping and spraying 3 to 4 times, and dried to obtain bacterial-loaded granules. The absorbance OD of the Bacillus pasteurianus liquid 600 It is 0.2~0.

8.

7. The self-repairing concrete according to claim 6, characterized in that: The preparation method of the Bacillus pasteurianus bacterial liquid is as follows: (1) Prepare solid culture medium: casein peptone 15 g / L, soy peptone 5 g / L, urea 20 g / L, agar powder 20 g / L; Prepare liquid culture medium: casein peptone 15 g / L, soy peptone 5 g / L, urea 20 g / L; After preparation, the culture medium was sterilized by high-pressure steam, and its pH value was adjusted after cooling. The pH value of the liquid culture medium was adjusted to 11, and the pH value of the solid culture medium was adjusted to 8, 9, 10, 11, 12, and 13 respectively; (2) dropping a suspension of Bacillus pasteurianus onto the solid culture medium with a pH of 8 prepared in step (1), and culturing the culture medium at a constant temperature of 30°C for 48 hours to obtain a Bacillus pasteurianus sample; (3) The Bacillus pasteurianus sample obtained in step (2) is continuously inoculated onto a solid culture medium with a pH value of 9. According to this step, the Bacillus pasteurianus is continuously inoculated onto a solid culture medium with a higher alkalinity. After each inoculation, the culture is cultured at the same constant temperature of 30°C for 48 hours. This cycle is repeated until the Bacillus pasteurianus can grow well on the high alkalinity flat culture medium with a pH value of 13, and the acclimation of the Bacillus pasteurianus to alkalinity resistance to pH value 13 is successfully completed. (4) The Bacillus pasteurianus sample plate coated on the solid culture medium with a pH of 13 was inoculated into the liquid culture medium with a pH of 11. The inoculated culture medium was placed in a constant temperature shaking incubator and cultured at 120 r / min at 30°C for 48 hours to obtain the Bacillus pasteurianus bacterial liquid.

8. The self-repairing concrete according to claim 1, characterized in that: The cement is PO42.5 ordinary Portland cement, and the fly ash is Class II fly ash.

9. The self-repairing concrete according to claim 1, wherein: Among the stones, the mass ratio of small stones to medium stones is 4:6; the fineness modulus of the small stones is 2.69-2.73, and the average particle size is 0.35~0.5cm; the particle size of the medium stones is 5~20mm.

10. A method for preparing fiber-modified self-repairing concrete, characterized in that: 750-800 parts of bacteria-loaded particles, 500-800 parts of modified basalt fibers, 870-1140 parts of water, 2700-2850 parts of cement, 650-720 parts of fly ash, 7100-7600 parts of sand, 113400-115400 parts of gravel, 55-80 parts of calcium lactate, 19-25 parts of water reducer, 9-14 parts of urea, and 1-5 parts of air-entraining agent are mixed, stirred evenly, and poured into a mold. After the specimen is formed, it is cured to obtain the self-repairing concrete.

Citation Information

Patent Citations

  • Microbial self-repairing concrete and preparation method thereof

    CN112500074A